Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/1468-2427.12376
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding the ‘SoHo Effect’ in Baltimore: Neighborhood Revitalization and Arts and Entertainment Districts

Abstract: This article investigates how state‐sponsored ‘arts and cultural districts' and ‘creative placemaking' revitalization strategies affect urban neighborhoods, using the Station North Arts & Entertainment (A&E) District in Baltimore, Maryland (USA) as a case study. Through ethnographic participatory methods and 39 qualitative interviews, we studied the activities and attitudes of various stakeholders within Station North. Since its designation as an arts and entertainment district in 2002, a number of public–priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The literature shows that it can come from a variety of sources, from municipal agencies (Babey and Giauque 2009), regions (Kavaratzis and Kalandides 2015), or entire countries (Papadopoulos and Heslop 2002). At the local level, branding and rebranding neighborhoods has become a key strategy for revitalizing arts and entertainment districts (Rich and Tsitsos 2016) as well as working-class immigrant communities (Wherry 2011).…”
Section: Place Brandingmentioning
confidence: 99%
“…The literature shows that it can come from a variety of sources, from municipal agencies (Babey and Giauque 2009), regions (Kavaratzis and Kalandides 2015), or entire countries (Papadopoulos and Heslop 2002). At the local level, branding and rebranding neighborhoods has become a key strategy for revitalizing arts and entertainment districts (Rich and Tsitsos 2016) as well as working-class immigrant communities (Wherry 2011).…”
Section: Place Brandingmentioning
confidence: 99%
“…Non-food-related designations in the literature include designations such as floodplain (Meldrum, 2016), conservation area (Ahlfeldt et al, 2017), historic district (Angjellari-Dajci and Cebula, 2016), arts and cultural district (Rich and Tsitsos, 2016), ozone non-attainment (Sheriff, Ferris, and Shadbegian, 2019), and enterprise zone designation (Zhang, 2015). The studies investigate the impacts of designations on a variety of outcome variables such as real estate value, employment, and income.…”
Section: Related Literaturementioning
confidence: 99%
“…For example, Angiellani-Dajci and Cebula (2016) investigate the impact of national historic district designation on the sales price of residential properties in St. Augustine, Florida, and conclude that the property sales prices are positively affected by various historical designations. Rich and Tsitsos (2016) conduct a case study of Station North Arts and Entertainment District in Baltimore, Maryland, and conclude that home values have increased in Station North since the Art and Entertainment District designation. Zhang (2015) studies the impact of the Louisville Enterprise Zone program on the growth of different industries and concludes that the enterprise zone program has significantly increased the growth of service and manufacturing activities in Louisville.…”
Section: Related Literaturementioning
confidence: 99%
“…The negative perspective some neighborhood stakeholders have regarding gentrification in Station North (and its resultant resident and business displacement) means that anchor institutions involved in community development must walk a fine line between revitalization and gentrification. We have explored this issue previously (Rich & Tsitsos, 2016) and have found that it is an almost impossible task, given the diverse interests of the stakeholders in Station North. At the interpersonal level, neighborhood residents, including longtimers, newcomers, and artists, engage in give-and-take in their interactions with each other.…”
Section: University-driven Development In Station Northmentioning
confidence: 99%
“…The three main players in the area-MICA, JHU, and University of Baltimore (UB)have dedicated many resources in Station North, even though none of these institutions situate their main campuses in this neighborhood. UB, a public Reprinted from Rich, M. A., & Tsitsos, W. (2016). Avoiding the "SoHo Effect" in Baltimore: Neighborhood revitalization and arts & entertainment districts.…”
Section: Introductionmentioning
confidence: 99%